ROZWIĄŻ RÓWNANIA
1 7x-3=x-2(5x-1)

2 x/3 - x-3/6 =4

3 -7(x+2)+4=-3x

4 -4 (1/2x-2)-4=2(-x+2)

5 3/2x + 0.7 = -0.3 x - 3/4

6 3x+2 = 12x+8/4


Odpowiedź :

Odpowiedź:

1) 7x-3=x-2(5x-1)

7x-3=x-10x+2

7x+9x=2+3

16x=5/:16

x=5/16

2) x/3 - x-3/6 =4/*6

2x-6x-3=24

-4x=24+3

-4x=27/:(-4)

x=-27/4=-6 3/4

3) -7(x+2)+4=-3x

-7x-14+4=-3x

-7x+3x=10

-4x=10/:(-4)

x=-10/4

x=-2 1/2

4) -4 (1/2x-2)-4=2(-x+2)

-2x+8-4=-2x+4

-2x+2x=4-4

0=0

x∈R

5 )3/2x + 0.7 = -0.3 x - 3/4/*4

6x+2,8=-1,2x-3

6x+1,2x=-3-2,8

7,2x=-5,8/:7,2

x=- 0,805

6 )3x+2 = 12x+8/4

3x-12x=2-2

-9x=0/:(-9)

x=0

Szczegółowe wyjaśnienie: